Six-Minute Walk Performance and Related Factors in Pediatric-Onset Multiple Sclerosis. (April 2022) - Zenginler Yazgan, Yonca; Vural, Pelin; Ormen, Recep; Akinci, Buket; Tarakci, Ela; Guler, Serhat; Saltik, Sema
Objective: To investigate functional exercise capacity and its relationship between physical activity levels, muscle strength, balance, fatigue, and quality of life in patients with pediatric-onset multiple sclerosis. Methods: Fifteen patients with pediatric-onset multiple sclerosis were included. The 6-minute walk test was used to determine functional exercise capacity and walking distance. The Godin Leisure-Time Exercise Questionnaire and pedometer were used to evaluate physical activity, Timed-Up and Go for dynamic balance, isokinetic testing for lower extremity muscle strength, Fatigue Severity Scale for fatigue, and the Pediatric Quality of Life Inventory (PedsQL) for quality of life. Results: The 6-minute walking distance was positively correlated with GLTEQ and the School-Work subgroup score of the PedsQL-Self-report, and negatively correlated with Timed-Up and Go and Fatigue Severity Scale. Dynamic balance, physical activity, and fatigue were significant predictors of 6-minute walking distance. Conclusions: Our results showed that 6-minute walk test is influenced by physical activity, dynamic balance, and fatigue, and related to quality of life in patients with pediatric-onset multiple sclerosis.